Comparison of bismuth and concomitant therapy for H. pylori eradication: a prospective, randomized clinical trial - A. Oueslati; G. Mohamed; S. Bostani; K. Boughoula; S. Bizid; H. Ben Abdallah; R. Bouali; M.N. Abdelli (Future Science OA, 2025)
Background In Tunisia, concomitant quadruple therapy (QTC) has been the standard first-line treatment for Helicobacter pylori (H. pylori) infection. However, increasing resistance to clarithromycin (28%) has raised concerns about its long-term efficacy. Bismuth-based quadruple therapy (QTB) offers an alternative, yet its higher cost and safety profile remain debated. This study aimed to compare the efficacy, safety, and cost of both regimens.Methods We conducted a prospective, randomized, open-label study enrolling 200 patients naïve to any anti-HP treatment. Patients were randomized to either 10 days of bismuth therapy (QTB: potassium bismuth subcitrate, metronidazole, and tetracycline hydrochloride, omeprazole) or 14 days of concomitant quadruple therapy (QTC: amoxicillin, clarithromycin, metronidazole, esomeprazole). H. pylori eradication as defined by a negative urea breath test 4-6 weeks after treatment.Results Among 200 patients, the intention-to-treat eradication rate was 82% for QTC and 87% for QTB (p = 0.29); per-protocol rates were 84.53% and 89.58%, respectively (p = 0.39). Compliance was high (97% in QTC vs 96% in QTB; p = 0.32). Adverse events were similar between groups (61.85% for QTB vs 69% for QTC; p = 0.29).Conclusion Bismuth and concomitant quadruple therapies were comparable in terms of efficacy and safety but didn’t achieve the accepted minimum eradication rate (90%).